2020
DOI: 10.33495/jacr_v8i9.20.173
|View full text |Cite
|
Sign up to set email alerts
|

Herbicidal effects of Prosopis juliflora (Sw.) DC. (Mesquite) leaf powder on seed germination and seedling growth of the weed species Tribulus terrestris L.

Abstract: Herbicidal effects of Prosopis juliflora (Sw.) (mesquite) leaf extract on seed germination and seedling development of the weed species Tribulus terrestris L. was investigated as a potential tool to control this widespread weed in the agricultural system of Tabuk region and many areas around the world. 5 T. terrerestris spiny seedcontaining fruits were germinated in 998, 995, 990 and 985 g soil mixed with 2 .00, 5.00, 10.0 and 15.00 g mesquite leaf powder respectively with three replicates in addition to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Besides, allelochemicals' production explained the reduction in the abundance of several species associated with P. juliflora (Kumar and Mathur 2014). Several studies showed that litter leachates and aqueous extracts of P. juliflora inhibited or significantly reduced seed germination of many associated natives, cultivated species and weeds (Noor et al 1995;Chellamuthu et al 1997;Al-Humaid and Warrag 1998;Edrisi et al 2020;Elbalola 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, allelochemicals' production explained the reduction in the abundance of several species associated with P. juliflora (Kumar and Mathur 2014). Several studies showed that litter leachates and aqueous extracts of P. juliflora inhibited or significantly reduced seed germination of many associated natives, cultivated species and weeds (Noor et al 1995;Chellamuthu et al 1997;Al-Humaid and Warrag 1998;Edrisi et al 2020;Elbalola 2020).…”
Section: Introductionmentioning
confidence: 99%